Substrate Specificity of Cysteine Proteases Beyond the S2 Pocket: Mutagenesis and Molecular Dynamics Investigation of Fasciola hepatica Cathepsins L - Corvo, Ileana; Ferraro, Florencia; Merlino, Alicia; Zuberbühler, Kathrin; O'Donoghue, Anthony J.; Pastro, Lucía; Pi-Denis, Natalia; Basika, Tatiana; Roche, Leda; McKerrow, James H.; Craik, Charles S.; Caffrey, Conor R.; et al. (Frontiers in Molecular Biosciences, 2018)
Cysteine proteases are widespread in all life kingdoms, being central to diverse physiological processes based on a broad range of substrate specificity. Paralogous Fasciola hepatica cathepsin L proteases are essential to parasite invasion, tissue migration and reproduction. In spite of similarities in their overall sequence and structure, these enzymes often exhibit different substrate specificity. These preferences are principally determined by the amino acid composition of the active site’s S2 subsite (pocket) of the enzyme that interacts with the substrate P2 residue. Although secreted FhCL1 accommodates aliphatic residues in the S2 pocket, FhCL2 is also efficient in cleaving proline in that position. To understand these differences, we engineered the FhCL1 S2 subsite at three amino acid positions to render it identical to that present in FhCL2. The substitutions did not produce the expected increment in proline accommodation in P2. Rather, they decreased the enzyme’s catalytic efficiency towards synthetic peptides. Nonetheless, a change in the P3 specificity was associated with the mutation of Leu67 to Tyr, a hinge residue between the S2 and S3 subsites that contributes to the accommodation of Gly in S3. Molecular dynamic simulations highlighted changes in the spatial distribution and secondary structure of the S2 and S3 pockets of the mutant FhCL1 enzymes. The reduced affinity and catalytic efficiency of the mutant enzymes may be due to a narrowing of the active site cleft that hinders the accommodation of substrates. Because the variations in the enzymatic activity measured could not be exclusively allocated to those residues lining the active site, other more external positions might modulate enzyme conformation, and, therefore, catalytic activity.